A bibliological note on P.Oxy. 659 (Pindar, Partheneia) - Prodi, EE (Siciana University Press, 2015)
The article re-assesses the evidence for the original format of P. Oxy. IV 659, argues that its columns had 28 to 29 lines each, suggests that the two poems it preserves were the second and third of the book, and briefly entertains the possibility that Pindar’s Partheneia may have been ordered alphabetically by title.